Early time to recurrence predicts worse survival in patients with localized or regionally advanced cutaneous melanoma. Issue 4 (24th May 2021) - Liang, Chengcai; Hu, Wanming; Li, Jingjing; Zhang, Xiaoshi; Zhou, Zhiwei; Liang, Yao
Abstract: To investigate the prognostic significance of time to recurrence (TTR) for overall survival (OS) and survival after recurrence (SAR) in patients with localized or regionally advanced cutaneous melanoma. A total of 731 cutaneous melanoma patients with an initial diagnosis of 8th American Joint Committee on Cancer (AJCC) clinical stage I‐III were included in this study. The prognostic factors associated with OS and SAR were estimated through Kaplan‐Meier and Cox regression analysis. Of the total cohort, 329 patients (45%) died, and 418 patients (57%) experienced recurrence. The median follow‐up and TTR were 55.6 months and 9.6 months, respectively. A total of 141 patients (19%) experienced recurrence in <6 months, and 277 patients (38%) experienced recurrence in ≥6 months. Patients with stage III and positive lymph node dissection (LND) were more common in the early TTR group than in the late TTR group. Both the OS and SAR rates at 5 years and 10 years in the early TTR group were significantly poorer than those in the late TTR group ( P < .001 and P = .008, respectively). Furthermore, early TTR, along with truncal tumor, higher TNM stage and therapeutic variables (extended resection, LND and adjuvant therapy), were significant independent predictors of worse OS and SAR in multivariate analysis (all P < .05). Early TTR predicts worse survival and could be considered an independent prognostic factor for patients with localized or regionally advanced cutaneous melanoma. TTR should be evaluated in all patients with recurrence to guide post‐recurrence risk stratification and follow‐up schedules.